External Quality Assessment of Molecular Typing of Staphylococcus aureus Isolates by a Network of Laboratories - Deplano, A. (American Society for Microbiology, 2006)
A network of laboratories designated Centres for Molecular Diagnosis was funded in 2000 by Belgian National Health Insurance to provide clinically relevant molecular diagnostic tests. These included typing of nosocomial pathogens as a service to local hospital infection control programs. Two external quality assessment (EQA) surveys were performed in 2001 and 2003 to evaluate the proficiencies of the laboratories at Staphylococcus aureus typing. EQA panels included S. aureus isolates with either indistinguishable, clonally related, or unrelated pulsed-field gel electrophoresis (PFGE) patterns. A hypothetical hospital outbreak problem was also submitted for analysis. Typeability, reproducibility, discrimination (D) index, and epidemiological concordance were evaluated. Ten centers participated in each survey. Seven centers performed PFGE analysis, while others used repetitive-element or randomly amplified polymorphic DNA PCR, amplified fragment length polymorphism, or spa typing. Full typeability (100%) was achieved by all centers, and all but one showed 100% reproducibility. Discrimination was appropriate (D index, ≥96%) for centers performing PFGE analysis but not for all those using other methods (D index range, 72% to 97%). Correct answers to the epidemiological questions were provided by 7/10 and 10/10 centers in 2001 and 2003, respectively. Individual feedback of results was provided to each center together with specific technical recommendations for improving performance. Our findings indicate that surveys of lab proficiency are useful for validation and optimization of molecular typing services to local hospital infection control programs.